Ispol'zovanie giperbariceskoj oksigenacii i normobariceskoj jipoksii v podgotovke sportsmenov - Ozolin, E. S. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The adaptation to the hypoxia, carried out in conditions of high-mountainous camps within 2-3 weeks, allows athletes to achieve best results at the competitions, which take place on the sea level. Recently many athletes use the method of normobaric hypoxia besides the widely spread method of training in conditions of high mountains.